Электронное правительство и социальная удовлетворенность: анализ социальных условий Тихуаны - Алма Беатрис Наварро; Мартин Кутберто Вера; Хулио Сезар Лопес (Вопросы государственного и муниципального управления, 2018)
This work explores the social elements that characterize the city of Tijuana, with the purpose of understanding ifthere is a disposition related to social capacities for the implementation of an electronic government. In the first part, a theoretical and contextual analysis of electronic government is made; afterwards the data obtained for Tijuana is analyzed as a result of a direct investigation in Baja California, with an emphasis on Tijuana. The main finding is whether or not the social conditions exist to make an implementation of an effective electronic government in Tijuana. The mixed methodology used part of Gurr’s postulate regarding the link between relative deprivation and social conflict and we hypothesized that it is required to have a medium-high degree of social satisfaction in order to make the implementation of an electronic government.